Cu / Zn / Al catalyst and preparation method thereof

By reducing the formation of hydrotalcite-like structures and increasing the formation of orthogonal green copper zinc ore and malachite structures, the problem of insufficient activity and stability of Cu/Zn/Al catalysts in low-temperature water gas transformation reaction is solved, and efficient CO is achieved Improved conversion rate and catalyst performance.

CN119281335APending Publication Date: 2025-01-10HEESUNG CATALYSTS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411546671.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-29
Filing Date
2024-11-01
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

When the existing Cu/Zn/Al catalysts improve durability, the problem of degradation of catalyst performance is due to the formation of hydrotalcite-like structures and the lack of catalyst activity and stability in the low-temperature water gas transformation reaction.

Method used

By reducing the formation of hydrotalcite-like structures and increasing the formation of orthogonal green copper zinc ore and malachite structures, the Cu/Zn/Al catalyst preparation method is used, including co-deposition, maturation and calcination steps, controlling the metal ratio and precipitant concentration, Avoid the generation of adverse crystalline structures.

Benefits of technology

High catalyst activity and durability in the low temperature range of 200°C to 300°C were achieved, and the CO conversion rate was increased to 94.84%, which significantly improved the performance and stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281335A_ABST
    Figure CN119281335A_ABST
Patent Text Reader

Abstract

The invention provides a Cu / Zn / Al catalyst, a preparation method of the Cu / Zn / Al catalyst and a method for converting the Cu / Zn / Al catalyst into hydrogen and carbon dioxide through reaction of carbon monoxide and water at low temperature by using the Cu / Zn / Al catalyst. The present invention minimizes the formation of a specific crystal structure which is unfavorable for active metal dispersion, and has high catalyst activity and durability in a low temperature field of 200 DEG C to 300 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention provides a low-temperature water-gas shift catalyst composition, a preparation method thereof and a method for using the catalyst to convert carbon monoxide and water into hydrogen and carbon dioxide at low temperature. Background Art

[0002] When the supply technology of hydrogen as fuel cell fuel is applied to the LNG fuel reforming system, if the carbon monoxide (CO) in the components of the mixed gas produced by the fuel reforming system flows into the fuel cell at a concentration above the base concentration of the fuel cell, the fuel cell electrode catalyst will be poisoned and its activity will be reduced. In the worst case, it will lead to permanent performance degradation. Therefore, the performance and stability of the water-gas shift catalyst used for removing CO in the fuel reforming system are very important.

[0003] Water-gas shift reaction: CO+H2O→CO2+H2(△H=-41kJ / h)

[0004] As a catalyst suitable for the low-temperature water-gas shift reaction at 200° C. to 300° C. for removing a small amount of carbon monoxide, Cu / Zn / Al-based catalysts are relatively well known.

[0005] International patent application publication WO 2020 / 080775 discloses a method for preparing a medium-temperature water-gas shift reaction catalyst for preparing hydrogen from carbon monoxide. Specifically, the method for preparing a water-gas shift reaction catalyst disclosed therein includes the following steps: a copper-zinc co-precipitation step of mixing a metal precursor solution containing a copper (Cu) precursor and a zinc (Zn) precursor with a precipitant solution to generate a copper-zinc co-precipitate; an Al precipitation step of injecting an aluminum (Al) precursor solution into a solution containing the copper-zinc co-precipitate so that aluminum is precipitated onto the surface of the copper-zinc co-precipitate to prepare a CuZnAl catalyst precursor having an aluminum-rich layer on the surface; and a calcination step of calcining the CuZnAl catalyst precursor to prepare a CuZnAl catalyst. Moreover, international patent application publication information WO 2022 / 069854 discloses a method for preparing a copper-containing catalyst for water-gas shift reaction and methanol synthesis, which is a two-step co-precipitation method, comprising the following steps: (a) a step of combining a first alkaline precipitant solution and an acidic copper-containing solution in a first precipitation step for forming a first precipitate; (b) a step of combining a second alkaline precipitant solution and an acidic aluminum-containing solution comprising one or more metal compounds selected from copper compounds, zinc compounds and promoter compounds in a second precipitation step for forming a second precipitate; (c) a step of contacting the first and second precipitates in a mixing step for forming a catalyst precursor; (d) a step of washing, drying and calcining the catalyst precursor; a silica precursor is included in the first precipitation step, the second precipitation step or the mixing step. Summary of the invention

[0006] The existing Cu / Zn / Al ternary catalyst has the problem that the Al content is proportional to the catalyst durability but inversely proportional to the catalyst performance. The present inventors have confirmed the following fact in the process of searching for the reason why the catalyst performance is reduced due to the increase of Al content in the experiment of improving the performance of CuZnAl catalyst, that is, if the Al content is reduced in the preparation process of CuZnAl catalyst and the formation of CuZnAl catalyst precursor with a specific crystal structure is suppressed, a catalyst that can ensure the durability of the catalyst and make the catalyst performance excellent can be prepared.

[0007] Specifically, it was confirmed that the problem of reduced catalyst performance caused by increasing the content of Al added to improve the durability of the CuZnAl catalyst is due to the formation of a precursor having a hydrotalcite-like structure. The present inventors have completed the present invention by establishing a method for preparing a CuZnAl catalyst that does not form a hydrotalcite-like precursor or minimizes its formation.

[0008] The present invention provides a Cu / Zn / Al catalyst, which is a Cu / Zn / Al catalyst for water-gas shift reaction and does not have a hydrotalcite-like or aurichalcite crystal structure.

[0009] The present invention provides a Cu / Zn / Al catalyst, which is a Cu / Zn / Al catalyst for water-gas shift reaction and has a crystalline structure of rosasite and malachite.

[0010] The present invention provides a method for preparing a water-gas shift catalyst, which minimizes the formation of precursors of hydrotalcite-like or chalcocite crystal structures and maximizes the formation of precursors of orthorhombic chalcocite and malachite crystal structures, especially greatly increases the generation of orthorhombic chalcocite.

[0011] Finally, the present invention provides a method for preparing hydrogen at low temperature by reacting the catalyst of the present invention or the catalyst prepared according to the method of the present invention with a mixed gas for water-gas shift reaction.

[0012] The water-gas shift reaction catalyst of the present invention minimizes the formation of a specific crystal structure that is unfavorable for the dispersion of active metals and has high catalyst activity and durability in the low temperature range of 200° C. to 300° C. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1The rosasite crystal structure, which is most favorable for the activity of Cu / Zn / Al ternary catalyst, is shown.

[0014] Figure 2 The standard X-ray diffraction patterns (XRD patterns) of the catalyst according to the present invention (improved catalyst) in which the formation of hydrotalcite-like precursors is suppressed and the catalyst according to the conventional co-precipitation method (conventional catalyst) are compared.

[0015] Figure 3 The CO conversion rates of a plurality of catalysts synthesized in a plurality of examples and a plurality of comparative examples are shown. DETAILED DESCRIPTION

[0016] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings. However, the embodiments of the present invention may be modified in various forms, and the scope of the present invention is not limited to the embodiments described below.

[0017] (definition)

[0018] The term "coprecipitation" used in the present invention can also be explained as "precipitation", and "precursor" means a substance in a precipitated state in a step before forming a finished catalyst in the form of a metal oxide. The terms "catalyst" and "catalyst composition" in the present invention have the same meaning. The metal ratio in this patent application means the ratio of the various metal oxides constituting the catalyst, that is, it means the weight ratio of CuO:ZnO:Al2O3, which can be simply marked as Cu:Zn:Al.

[0019] In the preparation process of CuZnAl catalyst, the crystal structures of multiple precursors that can be formed by Cu / Zn / Al vary depending on the composition of the starting metals / precipitation and aging temperatures / pH of the co-precipitation solution, as shown in Table 1.

[0020]

Table 1

[0021] Malachite <![CDATA[(Cu)2(CO3)(OH)2]]> Rosasite (Zinc Malachite) <![CDATA[(Cu 1-x Zn x )2(CO3)(OH)2]]> Aurichalcite <![CDATA[(Cu 1-x Zn x )5(CO3)2(OH)6]]> Hydrozincite <![CDATA[(Zn)5(CO3)2(OH)6]]> Hydrotalcite-like <![CDATA[Zn6Al2(CO3)(OH) 16 4H2O]]>

[0022] The present inventors have confirmed the following: a hydrotalcite-like or chalcocite-like structure, which is a specific crystal structure formed in the process of preparing a low-temperature water-gas shift catalyst, is a structure that hinders the activity of the catalyst, and in particular, a hydrotalcite-like structure is a precursor that needs to be avoided most in the process of preparing a CuZnAl catalyst; and, an orthorhombic chalcocite-like or malachite structure is beneficial to the activity of the catalyst, and in particular, an orthorhombic chalcocite-like structure ( Figure 1 ) is the structure that is most beneficial to the catalyst activity.

[0023] The invention provides a method for preparing a CuZnAl catalyst which minimizes the generation of multiple precursors of hydrotalcite-like and chalcocite structures and generates precursors of orthorhombic chalcocite structures at a high ratio. The catalyst prepared according to the invention exhibits high stability and activity in a low-temperature water-gas shift reaction.

[0024] The Cu / Zn / Al catalyst preparation method according to the present invention is achieved through a specific precipitation (co-precipitation) process of injecting Cu, Zn and Al solutions and a precipitant and a subsequent specific aging process in order to maximize the formation of a precursor of an orthorhombic chalcocite crystal structure.

[0025] Specifically, as starting materials, Cu, Zn and Al solutions are used to form a plurality of non-crystalline precursors through a precipitation process, and a plurality of precursors are crystallized with a specific structure through an aging process. A plurality of crystalline precursors are completed as a catalyst in the form of a metal oxide through a calcination process, and the catalyst is activated through a reduction process. The inventors have developed a CuZnAl catalyst preparation method by minimizing the formation of precursors of hydrotalcite or chalcocite as a crystalline structure that hinders the activity of the catalyst and greatly increasing the formation of precursors of orthorhombic chalcocite as a crystalline structure that is beneficial to the activity of the catalyst through a specific precipitation process and a specific aging process of injecting Cu, Zn and Al solutions and precipitants.

[0026] Figure 2 The standard X-ray diffraction patterns (XRD patterns) of the catalyst prepared by the method for inhibiting the formation of hydrotalcite precursors (improved catalyst) and the catalyst prepared by the existing co-precipitation method (existing catalyst) are shown. The performance evaluation results show that the CO conversion rate of the improved catalyst is 94.84%, which is much higher than the CO conversion rate of the existing catalyst of 89.72%.

[0027] According to the CuZnAl catalyst prepared by the present invention, the starting precursors use Cu, Zn and Al solutions. The inventors use a one-step method to coprecipitate multiple starting precursors to form a non-crystalline precursor, which is transformed into a crystalline precursor through a aging process, and control the coprecipitation and aging process to minimize the formation of precursors of hydrotalcite or chalcocite as a crystalline structure that hinders the activity of the catalyst and greatly increase the formation of precursors of orthorhombic chalcocite as a crystalline structure that is beneficial to the activity of the catalyst.

[0028] The preparation method of the water-gas shift catalyst of the present invention comprises the following steps: a coprecipitation step, in which a metal precursor solution containing a Cu precursor, a Zn precursor and an Al precursor is mixed with a precipitant solution and copper, zinc and aluminum are coprecipitated to generate a CuZnAl catalyst precursor. A aging step, in which the CuZnAl catalyst precursor is aged to minimize the formation of a hydrotalcite-like or chalcocite precursor and maximize the formation of a chalcocite precursor. A calcination step, in which the CuZnAl catalyst precursor is calcined to prepare a CuZnAl catalyst.

[0029] 1) One-step co-precipitation of Cu, Zn and Al

[0030] The Cu, Zn, Al co-precipitation step injects the Cu precursor, Zn precursor and Al precursor into the precipitant solution and prepares the precipitate in a one-step method, prepares the Cu precursor, Zn precursor solution and Al precursor solution and injects the solution containing these metal precursors into the solution containing the precipitant to precipitate Cu, Zn and Al. The co-precipitation process is maintained at pH 7.5 at 50°C to 70°C for 2 hours to 5 hours.

[0031] The Cu precursor, Zn precursor or Al precursor may be nitrate, acetate or other water-soluble compounds or salts, but a metal precursor in the form of nitrate which is not catalytically toxic is preferred.

[0032] The optimal concentration of the solution containing the metal precursor is 1.2 M, but it can be adjusted after considering factors such as the solution maintenance state. The Cu / Zn / Al precursors can be added so that the weight ratio of CuO:ZnO:Al2O3 of the catalyst becomes the optimal weight ratio of 62:31:7, that is, although the optimal molar ratio of Cu:Zn:Al precursor is 60:30:10, it can be adjusted in consideration of the activity and stability of the completed catalyst.

[0033] Preferably, the precipitant is alkaline, and includes, for example, carbonate or bicarbonate of an alkaline metal or ammonium. Preferably, the concentration of the precipitant is about 1.0 M in order to achieve a desired pH of 7.5 after injection of the metal precursor.

[0034] 2) Ripening steps

[0035] The solution containing the copper-zinc-aluminum coprecipitate is synthesized and maintained at the same temperature as the coprecipitation step for 2 to 5 hours to minimize the formation of the precursors of hydrotalcite or chalcocite, which are crystalline structures that hinder the activity of the catalyst, and greatly increase the formation of the precursors of orthorhombic chalcocite, which is a crystalline structure that is beneficial to the activity of the catalyst. The formation of these precursors of specific structures can be confirmed by XRD.

[0036] Optionally, after the aging is completed, the reaction system is cooled at room temperature, and a filtering and washing step is performed to remove unnecessary ions other than the CuZnAl catalyst precursor obtained through the aging process. The CuZnAl catalyst precursor is placed in distilled water and stirred to dilute the unnecessary ions remaining in the precipitate, and the precipitate is recovered by a filtering device. The above-mentioned process is repeated several times. Next, in order to remove the moisture of the CuZnAl catalyst precursor, it can be dried in a furnace at a temperature of 120°C to 180°C.

[0037] 3) Calcination step

[0038] This step is a step of transforming the catalyst into an oxide form before activating the catalyst. The catalyst is calcined at 300°C to 400°C. The calcination temperature can be adjusted in consideration of the catalyst activity and stability.

[0039] The present invention is further described in detail below in conjunction with specific examples. The following examples are merely examples to help understand the present invention, and the scope of the present invention is not limited thereto.

[0040] Example 1

[0041] Solution preparation steps

[0042] The Cu / Zn / Al nitrate precursor was dissolved in water to form a 1.25M Cu / Zn / Al precursor solution. The Cu / Zn / Al precursors were added so that the weight ratio of CuO:ZnO:Al2O3 of the prepared catalyst was 62:31:7. For the precipitation of multiple metal ions, an aqueous solution of about 1.0M was prepared using an alkaline precipitant Na2CO3.

[0043] Precipitation step

[0044] First, a certain amount of distilled water is added to the co-precipitation reactor and heated to 60°C. After heating, the Cu / Zn / Al precursor solution and the Na2CO3 precipitant solution are simultaneously injected into the co-precipitation reactor. The input flow rate of the Cu / Zn / Al precursor solution is adjusted so that the total input time is 4 hours, and the input flow rate of the precipitant is adjusted so that the pH in the reactor is maintained at 7.5. At this time, the temperature is maintained at 60°C.

[0045] Aging steps

[0046] After the Cu / Zn / Al solution was added, the aging was carried out for 4 hours at 60°C, which was the same temperature as the initial co-precipitation reactor.

[0047] Cleaning and filtration steps

[0048] After aging, the mixture is filtered and washed to remove ions other than Cu / Zn / Al precipitates.

[0049] Drying Steps

[0050] This step removes moisture from the filtered precipitate and is performed at 120°C to 180°C. The analysis of the Cu / Zn / Al system precursor was performed on the product dried at 120°C.

[0051] Calcination step

[0052] The calcination step converts the hydroxycarbonate precursor into a metal oxide form and is performed at 350° C. in an oxygen atmosphere.

[0053] Example 2

[0054] Except that the aging time was 2 hours, the other procedures were the same as in Example 1.

[0055] Example 3

[0056] The same procedure as in Example 2 was followed except that the precipitation time was 2 hours.

[0057] Example 4

[0058] The same procedure as in Example 1 was performed except that the precipitation step was performed while maintaining the precipitation pH at 8.5.

[0059] Example 5

[0060] Except that the aging time was 2 hours, the other procedures were the same as in Example 4.

[0061] Example 6

[0062] Except for CuO:ZnO:Al2O3=56:37:7, everything else was carried out in the same manner as in Example 1.

[0063] Example 7

[0064] Except for CuO:ZnO:Al2O3=46.5:46.5:7, everything else was carried out in the same manner as in Example 1.

[0065] Comparative Example 1

[0066] Except for CuO:ZnO:Al2O3=64:32:4, everything else was carried out in the same manner as in Example 1.

[0067] Comparative Example 2

[0068] Except for CuO:ZnO:Al2O3=48:48:4, everything else was carried out in the same manner as in Example 1.

[0069] Comparative Example 3

[0070] Except for CuO:ZnO:Al2O3=58:29:13, everything else was carried out in the same manner as in Example 2.

[0071] Comparative Example 4

[0072] Except for CuO:ZnO:Al2O3=45:45:10, everything else was carried out in the same manner as in Example 4.

[0073] Comparative Example 5

[0074] Except for CuO:ZnO:Al2O3=43.5:43.5:13, everything else was carried out in the same manner as in Example 1.

[0075] The crystal structures and CO conversion rates of the catalysts synthesized in the embodiments and comparative examples are shown in Table 2. Figure 3 As shown in the figure. Examples 2 to 7 and Comparative Examples 1 to 5 were compared based on the CO conversion rate of the precursor components of Example 1. Regarding the CO conversion rate, the gas composition of H20.4751, CO 0.1272, CO20.0174, and H2O 0.3804 was implemented at GHSV 4500h-1 and reaction temperature 200°C. The ratio of the crystalline structure is quantified using the Rietveld refinement method. In this patent application, the ratio of the precursor refers to the ratio of each precursor relative to the majority of the crystalline structures formed during the catalyst preparation process, that is, relative to the total amount of 4 precursors of Malachite, Rosasite, Aurichalcite, and hydrotalcite-like precursors.

[0076] Example 1 is the optimal condition of the present invention, and the following describes multiple processes for designing the optimal conditions.

[0077] In Examples 1 to 3, catalysts were prepared by adjusting the input time and the aging time under the same ingredients. The shorter the total precipitation time, that is, the shorter the input time and the aging time, the higher the ratio of the hydrotalcite precursor to malachite and the lower the ratio of orthorhombic chalcopyrite. If the metal ions are precipitated by the precipitant and obtain appropriate energy, they can undergo structural changes or transformations to become metal precursors in other forms. According to Examples 1 to 3, it can be confirmed that the hydrotalcite precursor and malachite are decomposed / rearranged and structurally changed to orthorhombic chalcopyrite by aging.

[0078] In Example 1, Example 2, Example 4, and Example 5, the catalyst was prepared by adjusting the pH maintained at 8.5 during precipitation under the same components. Compared with Example 1, in Example 4, it was confirmed that chalcocite, which is rich in OH, was generated due to the influence of high pH. By comparing Example 4 with Example 5, it can be confirmed that malachite was changed to rhombic chalcocite during aging, and a part of it was changed to rhombic chalcocite after 2 hours of aging. In addition, by comparing Example 2 with Example 5, it can be confirmed that the change to rhombic chalcocite at high pH was relatively not smooth.

[0079] Catalysts were prepared after adjusting the Cu:Zn:Al composition ratio in Example 1, Example 6 and Example 7. Compared with Example 1, the production amounts of hydrotalcite-like precursor and chalcopyrite increased in Example 6. Although the ratio of hydrotalcite-like precursor decreased in Example 7, the ratio of chalcopyrite increased.

[0080] Compared with Example 1, Comparative Examples 1 and 3 maintained the Cu:Zn ratio at 2:1 and adjusted the ratio of aluminum oxide. When the ratio of aluminum oxide was reduced, the formation of hydrotalcite precursors was suppressed, and the formation ratio of rhombic chalcopyrite increased, showing a higher initial activity. However, due to the low content of aluminum oxide, the durability of the catalyst was reduced, and thus a higher catalyst deactivation was shown in the reaction. On the contrary, when the ratio of aluminum oxide was increased, the formation of hydrotalcite precursors was promoted, and the formation of rhombic chalcopyrite, which was beneficial to the dispersion of copper particles, was suppressed, resulting in low activity.

[0081] Example 7 and Comparative Examples 2 and 5 maintained the Cu:Zn ratio at 1:1 and adjusted the alumina ratio. In Comparative Example 2, which had a lower alumina ratio than the general one, the low alumina content suppressed the formation of the hydrotalcite precursor and increased the generation ratio of chalcopyrite to chalcopyrite, thereby showing a higher initial activity. However, due to the low alumina content, it eventually showed a higher deactivation. In Comparative Example 5, as the alumina content increased, the generation ratio of the hydrotalcite precursor increased, thereby showing a low activity.

[0082] Comparative Example 4 is a catalyst prepared under conditions of a Cu:Zn ratio of 1:1 and pH 8.5, and exhibits a high chalcocite formation ratio and a very low orthorhombic chalcocite formation ratio due to the high pH conditions that are conducive to the formation of chalcocite. Although it exhibits a high initial activity due to the excessive chalcocite content, a low conversion rate can be confirmed in the end due to catalyst deactivation.

[0083] Comparative Example 5 is a catalyst prepared under conditions of a Cu:Zn ratio of 1:1 and a high alumina ratio. It can be confirmed that a hydrotalcite precursor is formed due to the high alumina ratio, and it can be confirmed that chalcopyrite is not formed at all. A low CO conversion rate is exhibited due to a high hydrotalcite precursor ratio and a low chalcopyrite ratio.

[0084] The following is an analysis of the catalyst activity of multiple embodiments and multiple comparative examples of the present invention. The catalyst derived from rhombic chalcocite exhibits high activity. The catalyst derived from rhombic chalcocite exhibits high activity at the beginning of the reaction, but the activity decreases as the reaction proceeds, and the final result is that the catalyst exhibits lower activity. On the other hand, the catalyst derived from malachite exhibits intermediate activity and deactivation, so it is confirmed that Cu ions that do not form rhombic chalcocite are most favorable for forming malachite. The hydrotalcite precursor is usually composed of only Zn and Al, so the catalyst derived from the precursor cannot affect the dispersion of Cu. When the precursor is formed, Zn ions are consumed and it is judged that it is difficult to form rhombic chalcocite, which is beneficial to activity.

[0085] Therefore, the present inventors set the Cu:Zn ratio to 2:1, the weight ratio of aluminum oxide to 7%, the pH of the co-precipitation reaction to 7.5, and the aging time to 4 hours as in Example 1, thereby minimizing the formation of hydrotalcite precursors and chalcopyrite and maximally increasing the formation of orthorhombic chalcopyrite, thereby preparing a catalyst exhibiting a high CO conversion rate and low initial catalyst deactivation.

[0086]

Table 2

[0087]

Claims

1. A Cu / Zn / Al catalyst, characterized in that: It is a Cu / Zn / Al catalyst for water-gas shift reaction, which does not have a hydrotalcite-like or chalcocite crystal structure.

2. A Cu / Zn / Al catalyst, characterized in that: It is a Cu / Zn / Al catalyst for water-gas shift reaction, which has only orthorhombic chalcocite and malachite crystal structures.

3. A Cu / Zn / Al catalyst, characterized in that: The invention relates to a Cu / Zn / Al catalyst for water-gas shift reaction, which has a 65% orthorhombic chalcopyrite crystal structure.

4. The Cu / Zn / Al catalyst according to any one of claims 1 to 3, characterized in that The Cu:Zn:Al ratio is 1:(0.5~1):(0.08~0.11).

5. A method for preparing a Cu / Zn / Al catalyst, characterized in that: The following steps are involved: A co-precipitation step, mixing a metal precursor solution containing a Cu precursor, a Zn precursor and an Al precursor with a precipitant solution and co-precipitating copper, zinc and aluminum to generate a CuZnAl catalyst precursor; A aging step, aging the precipitated CuZnAl catalyst precursor; In the calcination step, the matured CuZnAl catalyst precursor is calcined.

6. The method for preparing a Cu / Zn / Al catalyst according to claim 5, characterized in that: The co-precipitation step is performed at a temperature of 50° C. to 70° C. and the pH is maintained at about 7.5 for 2 to 5 hours.

7. The method for preparing a Cu / Zn / Al catalyst according to any one of claims 5 or 6, characterized in that: The aging step is maintained at a temperature of 50° C. to 70° C. for 2 to 5 hours.

8. A method for producing hydrogen, characterized in that: The following steps are involved: A catalyst according to any one of claims 1 to 3 or a catalyst prepared by the method according to claim 5 is provided and a water-gas shift reaction is carried out.

9. The method for producing hydrogen according to claim 8, characterized in that: The water-gas shift reaction is carried out at a temperature of 200°C to 300°C.

Citation Information

Patent Citations

  • Catalyst for water gas shift reaction at middle temperature, preparation method thereof, and hydrogen preparation method using same

    WO2020080775A1

  • Method for making copper-containing catalysts

    WO2022069854A1